Polymer chemistry - Koltzenburg, Sebastian, 1970-; Maskos, Michael, 1967-; Nuyken, Oskar, 1939- (Springer, 2017)
"This book is the English translation of the successful German textbook "Polymere", which was awarded the Chemical Industry in Germany’s 2015 literature Prize (“Literaturpreis des Fonds der Chemischen Industrie”) for its innovative, novel approach, and its good accessibility and readability, while at the same time providing comprehensive coverage of the field of polymer science."--Resumé vydavatele
Přeloženo z němčiny
Keywords: polymery; polymers; učebnice vysokých škol; textbooks (higher)